Determinants in the formation of extended and multifamily households in the Philippines - Tatum P. Ramos; Marife Magno-Ballesteros; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2024)
Nuclear households remain the dominant form of household type in the Philippines, but we note a rising number of extended and multi-family households, which have important implications on housing policy and demographic trends in the country. This study examines the factors influencing the decision to live in such household types. Multinomial logistic regressions are used to determine the association of potential factors with the formation of the extended and multi-family households. The results show that this formation is not necessarily a negative development as there are cultural factors that influence this arrangement but there is reason to believe that limited housing options in the market and the low attainability of homeownership for most individuals are driving the rise in extended and multi-family arrangements. There is a need for government to rethink its supply-driven housing policy in order to effectively respond to the housing need and the demographic changes that drives such need.
Keywords: 330; housing choice; extended households; demography; Philippines